2012
DOI: 10.1007/s00281-012-0351-7
|View full text |Cite
|
Sign up to set email alerts
|

Current understanding of immunity to Trypanosoma cruzi infection and pathogenesis of Chagas disease

Abstract: Chagas disease caused by Trypanosoma cruzi remains an important neglected tropical disease and a cause of significant morbidity and mortality. No longer confined to endemic areas of Latin America, it is now found in non-endemic areas due to immigration. The parasite may persist in any tissue, but in recent years there has been increased recognition of adipose tissue both as an early target of infection and a reservoir of chronic infection. The major complications of this disease are cardiomyopathy and megasynd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
193
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(210 citation statements)
references
References 173 publications
4
193
0
12
Order By: Relevance
“…These mononuclear cells infiltrating CCC heart tissue express predominantly interferon (IFN)-γ and tumor necrosis factor (TNF)-α, with lower levels of interleukin (IL)-2, IL-4, IL-6 and IL-10. Cytokines like IL-7 and IL-15, which promote T cell survival, are also found to have increased expression in CCC heart tissue [6,7] . Significant IFN-γ signaling was observed in the myocardium of CCC patients, including genes that are not ordinarily expressed by inflammatory cells [8] .…”
Section: Topic Highlightmentioning
confidence: 99%
“…These mononuclear cells infiltrating CCC heart tissue express predominantly interferon (IFN)-γ and tumor necrosis factor (TNF)-α, with lower levels of interleukin (IL)-2, IL-4, IL-6 and IL-10. Cytokines like IL-7 and IL-15, which promote T cell survival, are also found to have increased expression in CCC heart tissue [6,7] . Significant IFN-γ signaling was observed in the myocardium of CCC patients, including genes that are not ordinarily expressed by inflammatory cells [8] .…”
Section: Topic Highlightmentioning
confidence: 99%
“…Additional studies have demonstrated that auto-anti-idiotypic antibodies (Ids) from chagasic cardiac disease patients preferentially stimulate B1 cells and CD8 + T cells in magnified proportion as compared to indeterminate patients [29,30]. The lower levels of T cells in the peripheral blood of chagasic cardiac patients suggest that T-cell-mediated immunity should be restricted to inflammatory foci, considering previous reports of the presence of T cells, mainly CD8 + T lymphocytes, in the inflammatory infiltrate of cardiac tissue from individuals infected by T. cruzi [16]. A study using murine experimental model based on infection by T. cruzi demonstrated that the onset of cytokine production by T cells in the cardiac tissue is correlated with the local increase in the expression of cell adhesion molecules that is consistent with the T-lymphocyte migration to the inflammatory milieu [31].…”
Section: Physiology and Pathology Of Immunologymentioning
confidence: 82%
“…In fact, the disease outcome toward differential clinical forms is related to many factors including the host-parasite interaction. Several studies have been proposed that the host immunological response plays a major role in the pathogenesis of Chagas disease [16]. Indeed, the T. cruzi can trigger an immune response, since parasite antigen has been consistently found in heart tissue infiltrated from cardiac patients [17,18].…”
Section: Chagas Disease: An Outburst Of Inflammatory Events That May mentioning
confidence: 99%
See 1 more Smart Citation
“…hagas' disease, a major cause of morbidity and mortality in Latin America (1)(2)(3), is commonly transmitted by bloodsucking reduviid bugs, which, during a blood meal, release Trypanosoma cruzi. As a metacyclic trypomastigote, T. cruzi gains access to the body through mucosal surfaces or discontinuity in the skin, where it elicits a pronounced inflammatory response.…”
mentioning
confidence: 99%